Direct femtosecond laser printing of silk fibroin periodic structure with lower mid-infrared reflectivity - Couto, Filipe A.; Paula, Kelly T.; Santos, Moliria V.; Ribeiro, Sidney J.L. [UNESP]; Mendonça, Cleber R. (Elsevier, 2023)
Periodic dielectric structures offer an efficient way to control light propagation at micro- and nanoscale, also presenting low losses. Among many techniques that can produce such structures, femtosecond Laser-Induced Forward Transfer (fs-LIFT) is a promising one due to its relatively simple implementation and ability to process broad classes of materials, preserving their integrity. In particular, Silk fibroin (SF), a natural biopolymer, can be processed by fs-LIFT to print well-ordered periodic arrays of microstructures. Due to its high transparency, biocompatibility, and high possibilities of functionalization, SF is a suitable material for photonics. In this work, a 2D lattice of hemi-elliptical SF microdroplets was fabricated via fs-LIFT, and finite-element (FEM) simulations were carried out to study their response to electromagnetic radiation in the near to mid-infrared spectral region, considering the influence of the substrate. The simulation results indicated a decrease in reflectivity which was corroborated with experimental results. In addition, coating the fabricated structures with a higher index dielectric material was shown to enhance the decrease in reflectivity in the mid-infrared spectral region. These results demonstrate a straightforward way to print ordered arrays of SF microstructures in a relatively large area, with potential application as controllable reflectivity coating for the near to mid-infrared spectral region.